The Effect of Quantum Teaching Model with the Camtasia Instructional Media and Learning Motivation on PPKn Subject Learning Outcomes in 7th Grade Student of Junior High School PGRI 4 Medan - Ribka Meilan Siadari; Daulat Saragi; Dede Ruslan (BIRCU, 2019)
The aim of the study is to analyze the effect of the quantum teaching model with camtasia instructional media and learning motivation on PPKn subject learning outcomes. This study is conducted in 7th grade student of junior high school PGRI 4 Medan with a population of 46 students. The sample in this study were 39 students is using purposive random sampling technique. The instruments of this study are learning outcomes tests and learning motivation questionnaires. This study uses quasi-experimental methods, while the research design uses Non Equivalent Control Group Design. Data analysis techniques used in this study are descriptive analysis and also non-parametric inferential statistics. This study is based on the 2013 curriculum teaching which gives authentic assessment to students which includes cognitive, affective, and psychomotor domains, therefore this study presents the acquisition of learning outcomes in terms of cognitive, affective, as well as psychomotor. There are 3 hypotheses that have been proven in this study including: PPKn learning outcomes of students taught using Quantum Teaching models with camtasia instructional media is more higher than the PPKn learning outcomes of students taught by using Quantum Teaching models with media images, PPKn learning outcomes of students who have high learning motivation is more higher than students who have low learning motivation, and there is an interaction between the Quantum Teaching learning model and camtasia instructional media and learning motivation on the PPKn learning outcomes of 7th grade student of junior high school PGRI 4 Medan. The conclusion show that the use of the Quantum Teaching Model with camtasia instructional media and learning motivation is very effected in improving learning outcomes both cognitive, affective, and psychomotor.